The Postponed Regional Head Elections in Emergency Situations: a Constitutional Democracy Perspective in Indonesia - Fikri Ahsan; Wahyu Andrianto; Djarot Dimas Achmad Andaru; Mohamad Mohamad Hanapi (Yustisia, 2023)
The postponement of regional head elections may be done when the country is declared in a state of emergency. Emergencies such as war, economic crises, disease epidemics, and natural disasters affect the constitutional rights of citizens regulated by the 1945 Constitution. Therefore, legal instruments are needed to avoid unconstitutionality in fulfilling constitutional rights and democratic values during emergencies or dangers, including postponing regional elections during the COVID-19 pandemic.  Article 12 of the 1945 Constitution is the most relevant legal basis for activating emergency constitutional law   when   the   state   is  declared dangerous. However, Article 22 of the 1945 Constitution was preferred in postponing  regional  elections.  Even though the holding of elections itself is guaranteed by the constitution every five years, on the other hand, the constitution has not regulated the postponement of elections if the country is in danger or an emergency. So, in the future, there will need to be constitutional amendments and new regulations that further widen the spectrum of dangerous or emergency conditions without forgetting Article 12 of the 1945 Constitution as a consideration